2019
DOI: 10.1021/acsnano.9b04783
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel-Coated Microneedle Arrays for Minimally Invasive Sampling and Sensing of Specific Circulating Nucleic Acids from Skin Interstitial Fluid

Abstract: Minimally-invasive technologies that can sample and detect cell-free nucleic acid biomarkers from liquid biopsies have recently emerged as clinically useful for early diagnosis of a broad range of pathologies, including cancer. Although blood has been so far the most commonly interrogated body fluid, skin interstitial fluid has been mostly overlooked despite containing the same broad variety of molecular biomarkers originating from cells and surrounding blood capillaries. Minimally-invasive technologies have e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
169
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(170 citation statements)
references
References 60 publications
1
169
0
Order By: Relevance
“…Zhang et al devised encoded MNs capable of detecting multiple biomarkers such as tumor necrosis factor alpha (TNF‐α), interleukin 1β (IL‐1β), and IL‐6 26. Sulaiman et al developed MNs coated with an alginate‐peptide‐nucleic acid hybrid material for specific nucleic acid sampling and detection 27. Furthermore, the extraction of plant DNA by MNs was demonstrated for rapid detection of plant diseases 28…”
Section: Figurementioning
confidence: 99%
“…Zhang et al devised encoded MNs capable of detecting multiple biomarkers such as tumor necrosis factor alpha (TNF‐α), interleukin 1β (IL‐1β), and IL‐6 26. Sulaiman et al developed MNs coated with an alginate‐peptide‐nucleic acid hybrid material for specific nucleic acid sampling and detection 27. Furthermore, the extraction of plant DNA by MNs was demonstrated for rapid detection of plant diseases 28…”
Section: Figurementioning
confidence: 99%
“…In order to simplify postquantification of biomarkers, Zhang et al integrated the hydrogel MNs with photonic crystal barcodes, which enabled direct quantification of the biomarkers via the fluorescence of the barcodes . Moreover, Al Sulaiman et al coated the solid MNs with a layer of hydrogel which covalently connected with bespoke peptide nucleic acid (PNA) probes via a photocleavable linker . When MNs were in contact with the solution containing DNA, the DNA sequence of interest diffused into hydrogel matrix and hybridized to the probes to form the PNA:DNA complex.…”
Section: Biomedical Applications Of Microneedlesmentioning
confidence: 99%
“…When MNs were in contact with the solution containing DNA, the DNA sequence of interest diffused into hydrogel matrix and hybridized to the probes to form the PNA:DNA complex. The nonspecific DNA could be removed from MNs by simple washing ( Figure ) . There were two ways for quantification or analysis of these captured DNA.…”
Section: Biomedical Applications Of Microneedlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although state‐of‐the‐art MNs have greatly promoted sample extraction, [ 10–12 ] some limitations in the isolation of biomolecules exist. Consequently, some enhanced MN platforms approached these tedious problems by means of laser illumination, [ 13 ] multiple photonic crystal barcodes, [ 14 ] hydrogels, [ 15–17 ] and near infrared quantum dots. [ 18 ] Sulaiman et al first reported ultrafast MNs based on an alginate‐peptide hydrogel for sequence‐specific isolation, extraction, and detection of microRNA within 2 min.…”
Section: Introductionmentioning
confidence: 99%